In Search of the Imagined Ummah: Explaining the Political Crossover of Islamic Conservatism in Indonesia’s 2019 Presidential Election - Andar Nubowo (Journal of Asian Social Science Research, 2020)
It has been admitted that the 212 movements constituted not only a socio-religious driving force but also a political one in contemporary Indonesia. In the 2019 presidential election, conservative Islamic camps that had anger and resentments toward President Joko Widodo (Jokowi) as he was regarded incapable of solving crises and keen on discriminating against Islam and ulama came up together to win Prabowo Subianto-Sandiaga Uno. Based on qualitative field research in some areas of Indonesia, this article analyses the diffusion of some Islamic groups with their grand narratives and discourses, and their involvement in Prabowo-Sandiaga’s campaign, considered as a fast track of establishing a utopia of the imagined ummah (united Muslim community). In the light of an Islamic activism and social movement theory, it concludes that such a political crossover is a kind of new Islamic activism and social movement. It has not been merely rooted in a conservative outlook of Islam, but also in their dissatisfaction and contention over Jokowi’s social and economic policies. This kind of new Islamic social movement would affect contemporary Indonesian religious and political realms.